The Straits of Malacca : gateway or gauntlet? - Freeman, Donald B. (McGill-Queen's University Press, 2003)
For centuries the Straits of Malacca, a narrow waterway between the Malay peninsula and the island of Sumatra, has been both a major conduit for long distance trade between Asia and the West and one of the most dangerous areas for commercial shipping.